Breaking degeneracy in jet dynamics: multi-epoch joint modelling of the BL Lac PKS 2155–304. Issue 4 (30th October 2018) - Lucchini, M; Markoff, S; Crumley, P; Krauß, F; Connors, R M T
ABSTRACT: Supermassive black holes can launch powerful jets which can be some of the most luminous multiwavelength sources; decades after their discovery their physics and energetics are still poorly understood. The past decade has seen a dramatic improvement in the quality of available data, but despite this improvement the semi-analytical modelling of jets has advanced slowly: simple one-zone models are still the most commonly employed method of interpreting data, in particular for active galactic nucleus (AGN) jets. These models can roughly constrain the properties of jets but they cannot unambiguously couple their emission to the launching regions and internal dynamics, which can be probed with simulations. However, simulations are not easily comparable to observations because they cannot yet self-consistently predict spectra. We present an advanced semi-analytical model which accounts for the dynamics of the whole jet, starting from a simplified parametrization of relativistic magnetohydrodynamics in which the magnetic flux is converted into bulk kinetic energy. To benchmark the model, we fit six quasi-simultaneous, multiwavelength spectral energy distributions of the BL Lac PKS 2155–304 obtained by the TANAMI (Tracking Active Galactic Nuclei with Austral Milliarc-second Interferometry) program, and we address the degeneracies inherent to such a complex model by employing a state-of-the-art exploration of parameter space, which so far has been mostly neglected in the study of AGN jets. We find that this new approach is much more effective than a single-epoch fit in providing meaningful constraints on model parameters.